1981
DOI: 10.1042/bj1960811
|View full text |Cite
|
Sign up to set email alerts
|

Brain 5-aminolaevulinate synthase Developmental aspects and evidence for regulatory role

Abstract: 1. Brain 5-aminolaevulinate synthase showed a peak of increased activity in the first few weeks of life, which preceded and accompanied the development of brain cytochromes. 2. In the brain of the adult rat the activity of the enzyme was only 20% of that in the liver (on a per g wet wt. basis), but it was still probably sufficient to maintain the turnover of brain cytochromes. 3. The brain synthase activity could be decreased by treatment of rats with cycloheximide or with large doses of 5-aminolaevulinate, es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

1987
1987
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 34 publications
1
23
0
Order By: Relevance
“…For instance, it has been indicated that ALA inhibits glutamate uptake in differentiated astrocyte cultures by selectively affecting the GLT-1 subtype of glutamate transporter 101) , and that ALA can generate free radicals 102) . Also, previous studies have shown that ALA is generated even in the brain 103,104) . We may therefore hypothesize that lead impairs children's intelligence and neurobehavioral performance, possibly due to increased ALA in the brain, despite the presence of at least one animal experiment reporting that lead-induced cell death in the hippocampus in vivo may be partly due to apoptosis 105) .…”
Section: Lead Toxicity In Childrenmentioning
confidence: 99%
“…For instance, it has been indicated that ALA inhibits glutamate uptake in differentiated astrocyte cultures by selectively affecting the GLT-1 subtype of glutamate transporter 101) , and that ALA can generate free radicals 102) . Also, previous studies have shown that ALA is generated even in the brain 103,104) . We may therefore hypothesize that lead impairs children's intelligence and neurobehavioral performance, possibly due to increased ALA in the brain, despite the presence of at least one animal experiment reporting that lead-induced cell death in the hippocampus in vivo may be partly due to apoptosis 105) .…”
Section: Lead Toxicity In Childrenmentioning
confidence: 99%
“…Complex inhibitory effects of heme on hepatic ALAS1 include transcriptional, post-transcriptional and posttranslational events: a) inhibition of ALAS1 gene transcription, b) reducing mRNA stability, c) blocking mitochondrial import of ALAS1 thus preventing processing of the cytosolic precursor to the mature mitochondrial form, and d) inhibition of the ALAS1 enzyme activity by the end product negative feedback mechanism [66,67,69,76,77]. Heme is also a negative regulator of heme biosynthesis in the brain, but the mechanism of the inhibition is different from that of liver [51,64]. In olfactory receptor neurons, heme inhibited another enzyme of heme biosynthesis, ALA dehydratase that catalyzes conversion of 5-aminolevulinic acid to porphobilinogen [51].…”
Section: Heme As a Regulator Of Ho-2 Activitymentioning
confidence: 99%
“…In the brain, endogenous heme level is comparable with that of liver (1.3 nmol/mg protein [51]). ALAS1-mediated formation of endogenous heme is required for synthesis and catabolism of hemoproteins, such as nitric oxide synthase, cyclooxygenase, and mitochondrial cytochromes, essential in brain development and functions [51,64,[70][71][72]. Moreover, HO-catalyzed degradation of endogenous heme produces vasodilator, neuromediator, antioxidant and cytoprotective compounds critical for brain functioning.…”
Section: Heme As a Regulator Of Ho-2 Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Type 1 HMOX can be markedly induced under conditions of stress, thereby increasing the requirement for substrate (Sassa and Nagai, 1996;Sassa, 2004). In nonerythroid tissue, including brain, increased requirement for intracellular heme can be detected as up-regulation of the gene Alas1 for aminolevulinate synthase 1 (ALAS1), the first step of heme synthesis, and commonly accepted as a response to a lowered regulatory heme pool (De Matteis et al, 1981;De Matteis and Ray, 1982;Sassa and Nagai, 1996). The availability of heme may also be a limiting factor in the ability of neuronal cytochrome P450 enzymes to metabolize drugs and chemicals (Meyer et al, 2002).…”
mentioning
confidence: 99%